Effect of Covid-19 Pandemic to the Fishers in a Coastal Municipality in the Philippines - Naz, Graham M. (Future Science / FSH-PH Publications, 2022)
The fishing industry was not spared by threats of Covid-19 pandemic, despite being considered as part of essential industry. This study determined the effects of the pandemic to the fishing industry, particularly the fishers, in terms of their cost of operation, sales and volume of catch. It also identified their problems encountered and the strategies used to deal with the problems. The study employed descriptive quantitative research design. Respondents, who are the local fishers in a coastal municipality of Bulan, Sorsogon, Philippines, are randomly chosen through stratified random sampling. Survey questionnaire was used and data were analyzed through descriptive statistics. Results revealed that respondents had been heavily affected by the pandemic, particularly in their cost of operation among the three areas of concern. This was due to increase in prices of crude oil/gasoline, food commodities, and fishing gears and equipment. Only few respondents, however, expressed that there are effects on sales and volume of catch. Findings of the study revealed that most common problems were price increase in gasoline/crude oil and fishing gears, as well as price volatility of fish. Study found that respondents took loans (from loan sharks/brokers), repaired their fishing gears by themselves (instead of buying or paying for repair) and attend more to their alternative source of income, to overcome the challenges of pandemic to their livelihood. It recommends that local government must consider providing fishers with relief/loan assistance, particularly during state of calamities, as well as providing livelihood programs and skills training for more sustainable alternative source of income.